Penerapan Metode HIRARC untuk Analisis Risiko Keselamatan Kerja Pada Penambang Emas Rakyat di Ratatotok - Maikel Wahani (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
Traditionally, small-scale mining industry organized by the community is a typical industry that has a high risk of work accidents. Related to efforts to minimize the risk of mining activities in traditional mining businesses, this study aims to identify various safety risks in the traditional gold mining process in Ratatotok, North Sulawesi using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) method.Â The results of the application of this method indicate that the most critical risk of work accidents is the danger of being hit by a hole buffer tool and being pinched by rocks and the danger of being buried by landslides due to continuous rain with the largest risk score of 25.